LEGAL ANALYSIS OF APBDES CAPACITY IN INCREASING THE PRODUCTIVITY OF THE MARITIME ECONOMY IN SOUTH HALMAHERA DISTRICT - muhammad amin hanafi; imran ahmad; Nurlaila Kadarwati Pupulawa (Khairun Law Journal, 2023)
The role of the fisheries sector is very large in Morotai Island Regencymust be utilized as much as possible for the prosperity of society. So far, many fishery products have been stolen by foreign fishing boats. By opening up investment for fishing companies, diversifying the utilization and processing of marine products as well as providing assistance to local fish entrepreneurs and providing fishing gear assistance to fishermen is one of the solutions for the development of the fisheries sector in South Halmahera Regency which can be planned for the future.The research method used in this study is the normative legal research method as material to initiate researchers in carrying out an inventory of statutory approaches (statute approach), comparative law (comparative approach), and case studies (case approach). The characteristics of this study fully use secondary data, consisting of primary legal materials; secondary legal materials; as well as tertiary legal materials. The results of the research show that in practice, the development of maritime potential in South Halmahera Regency experiences various challenges and opportunities. Efforts to deal with these obstacles include moderating stakeholders to analyze and describe what is best for the development of maritime potential in South Halmahera Regency, North Maluku Province. It is very important to equate perceptions and common interests so that the policies that are being implemented can run well until the end. Carrying out bureaucratic reform by summarizing the administrative system, including mobile bureaucratic services, both at sea and on land by using boats/ships that are connected to services and the internet so that it makes service easier for the community. Next is to open up investment opportunities as wide as possible so that investment can come easily to the Bintan Regency area. With easy investment into then indirectly. will improve the economy of the people in South Halmahera Regency itself.The capital aspect can be overcome by providing financial assistance to fishermen. It can be in the form of distributing people's business credit, direct investment, CSR of large companies, or through fishing cooperatives where the government provides the widest possible capital assistance in the form of capital equipment and operational equipment such as boats, boat engines, nets, bait, navigational equipment, environmentally friendly technology, fuel, and processing plants and fish auctions which result in destructive fishing.